2021
DOI: 10.2478/gsr-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

Shared Metabolic Remodeling Processes Characterize the Transcriptome of Arabidopsis thaliana within Various Suborbital Flight Environments

Abstract: The increasing availability of flights on suborbital rockets creates new avenues for the study of spaceflight effects on biological systems, particularly of the transitions between hypergravity and microgravity. This paper presents an initial comparison of the responses of Arabidopsis thaliana to suborbital and atmospheric parabolic flights as an important step toward characterizing these emerging suborbital platforms and their effects on biology. Transcriptomic profiling of the response of the Arabidopsis eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…As far as research has heretofore determined, the profile of transcriptional changes in response to microgravity includes several themes, the first of which is cell wall synthesis and/or modification. Of the studies examined in this review, Califar et al (2021), Choi et al (2019), Jin et al (2018), Jin et al (2015), Johnson et al (2017), Kruse et al (2020), Manian at al. (2021), Manzano et al (2020), Paul et al (2017), Paul et al (2013b), andVillacampa et al (2021) all found a significant number of DEGs associated with cell wall synthesis and/or modification (Supplementary Table S1).…”
Section: Critical Analysis Of Recent Plant Spaceflight Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…As far as research has heretofore determined, the profile of transcriptional changes in response to microgravity includes several themes, the first of which is cell wall synthesis and/or modification. Of the studies examined in this review, Califar et al (2021), Choi et al (2019), Jin et al (2018), Jin et al (2015), Johnson et al (2017), Kruse et al (2020), Manian at al. (2021), Manzano et al (2020), Paul et al (2017), Paul et al (2013b), andVillacampa et al (2021) all found a significant number of DEGs associated with cell wall synthesis and/or modification (Supplementary Table S1).…”
Section: Critical Analysis Of Recent Plant Spaceflight Experimentsmentioning
confidence: 99%
“…Suborbital flights (those which do not reach escape velocity or become artificial satellites around Earth) can provide a reduced gravitational environment for a short time (i.e., a few minutes). Plants were flown on several different types of suborbital flights to determine how their transcriptomes were affected in each environment as compared to those on Earth and in microgravity (Califar et al, 2021). The flights tested included parabolic flights, the Virgin Galactic and Blue Origin suborbital flights, and the F-104 Starfighter flight, all of which create different cycles of hypergravity and microgravity along their flightpath.…”
Section: Transcriptomic Effects Of Microgravity In Suborbital Flightsmentioning
confidence: 99%
See 1 more Smart Citation
“…Virgin Galactic (VG) flies a spaceflight system consisting of a spaceship VSS Unity , along with a mothership, VMS Eve , to perform commercial suborbital flights. This unique platform delivers a suborbital spaceflight profile including a slight hyper- g of horizontal takeoff, a hyper- g during spaceship’s rocket motor boost to space, a 3–4 min microgravity period, and a re-entry with a mixture of hyper- and hypo- g segments prior to landing 1 , 2 . This platform allows customer-defined scientific experimental materials to be flown as automated hardware payloads, and also opens the door to researchers interacting with payloads to conduct experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Virgin Galactic’s chief space officer, George Whitesides, previously categorized space travel as an “out-of-home luxury experience,” the fastest-growing luxury market (Sheetz, 2021). The pricing varies based on the four levels of space travel—the parabolic flight, like the B727 aircraft; high-altitude flight close to space, like MiG-29 Jet; suborbital flights, like those launched by Virgin Galactic and Blue Origin; and orbital flight, such as flights launched by Space X (Califar et al, 2021; Crouch et al, 2009).
Figure 1.Space travel prices at different altitudes.
…”
Section: Introductionmentioning
confidence: 99%